Pelletizing of Various Municipal Solid Waste: Effect of Hardness and Density into Caloric Value - Suryawan, I.W.K. (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
Density and hardness are physical parameters in the manufacturing of refuse derived fuel (RDF) pellets. In making pellets, a high heating value for the combustion system is desired. This research aimed to analyze the mixture of municipal solid waste to its density and hardness and study its correlation to heating value. The variable used in this research is a mixture of paper waste and garden waste and food scraps and garden waste. The density and hardness for the mix of paper waste and garden waste were 1970.6 to 2474.8 kg/m3 and 37.8â42.8 HA, respectively. The mixture of food waste and garden waste has density and hardness of 1822 to 2276.7 kg/m3 and 17.4â37.8 HA. The correlation between density and hardness on heating values âdid not reach a significance of 0.05, so there was no strong relationship between density and hardness on heating values. Â© 2022, Polskie Towarzystwo Inzynierii Ekologicznej (PTIE). All rights reserved.